Synthesis and Identification of New Azolidine-4-one Derived from Creatinine and Study their Anticancer and Antioxidant Effects - Ali, Rana Abid; Al-Tamimi, Entesar O.; Abdul-Wadood, Shatha (Iraqi Journal of Science, 2023)
Creatinine and Schiff`s bases are well known for their diverse range of biological activities and are thought to be emerging and useful therapeutic targets for the treatment of several diseases. The present work was aimed at the synthesis of new imidazolidine-4-one, thiazolidine-4-one, and oxazolidine-4-one derivatives derived from creatinine and to illustrate their influence on a colon cancer cell line and assess their antioxidant activity. Creatinine was reacted with α-chloroethyl acetate to produce 2-ethyl acetate creatinine 1. Then, the reaction of compound  1 with n-propyl bromide afforded N-propyl-2-ethylacetate creatinine 2. Compound 2 was then reacted with hydrazine hydrate to give hydrazide derivative 3. Schiff bases 4-6 were synthesized via the reaction of compound 3 with aromatic aldehydes (benzaldehyde and p-hydroxybenzaldehyde) and a ketone (p-amino acetophenone) in the presence of glacial acetic acid as a catalyst. Finally, Schiff bases 4-6 were treated with 2-aminoacetic acid to synthesize imidazolidine-4-one derivatives 7-9, with 2-thioglycolic acid to prepare thiazolidine-4-one derivatives 10-12, and with glycolic acid to synthesize oxazolidine-4-one derivatives 13-15. The newly synthesized compounds were identified using FT-IR and 1H NMR spectroscopy. In addition, the antioxidant and anticancer activities of some of the synthesized compounds were evaluated in vitro and showed good results.